Reconceptualizing water governance through traditional knowledge: insights from Wayuu cosmovision in La Guajira, Colombia - Vargas-Chaves, Iván (Frontiers in Water, 2025)
This paper presents a conceptual analysis of critical water governance issues in La Guajira, Colombia, with a specific focus on the Wayuu's profound spiritual and relational conceptualization of water, which is largely unrecognized in prevailing top-down, techno-economic governance approaches. The primary objective is to conceptually explore the complexities of water governance, the unique Wayuu cosmovision of water, existing water management practices, and the traditional knowledge of community's, drawing extensively from foundational research and documentary sources. The methodology involved systematic review and synthesis of key scholarly documents to elaborate a conceptual framework. The principal conceptual finding is that the severe water scarcity crisis—characterized by insufficient, unacceptable, unhealthy, and inaccessible water—emerges not only from physical conditions but fundamentally from a conceptual misalignment. This misalignment is evident in institutional failures, and a systemic disregard for Wayuu ancestral knowledge. This analysis concludes that the current water crisis in La Guajira represents a violation of fundamental human rights, aggravated by the profound disconnect between state policy conceptualizations local cultural and socio-ecological realities.